DEPICTING WOMEN EMPOWERMENT IN BOCEK VILLAGE: THE STORY OF BU US - Agung, Ramadhan Permana; Nasvian, Moch. Fuad (KABILAH : Journal of Social Community, 2022)
Abstrak: The research entitled Depicting Women Empowerment in Bocek Village: The Story of Bu Us. This study is about a housewife that lives in Bocek Village, a rural area in Malang Regency, who works as an entrepreneur and tries to empower housewives in her village. The village community used to see that housewives just had a domestic role in the family. This research uses qualitative approach with phenomenological methods from the perspective of Bu Uswatun Hasanah or Bu Us. The findings of this research are the mentality of Bu Us, which never gives up under any circumstances, drives her to prove that she can accomplish anything independently rather than being a desperate housewife in order to become a tough woman to support her family as well as the Bocek Village community's economy. Her credo, "Mesti Iso" or "I Can Do It" inspired her to start her own business without the help of her closest relation including her own husband, by joining some organizations in her village and sub-district and organizing women empowerment events. Keywords: Phenomenology, Women Empowerment, Family Communication